The use of microalgae as the raw material of bioethanol - Assadad, Luthfi; Utomo, Bagus Sediadi Bandol; Sari, Rodiah Nurbaya (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2010)
Biofuel is one of alternative fossil fuel, in which the raw materials come from biological resources.One of the raw materials for biofuel production is microalgae. Microalgae grows rapidly, does notcompete with food for humans, and needs small areas to cultivate. Utilization of microalgae forbiofuel research nowadays is focusing on biodiesel production, but actually microalgae can beused to produce other biofuels such as bioethanol. The carbohydrate content of the microalgaecan be converted into glucose and fermented into alcohol. Carbohydrate content of the microalgaeis about 5.0–67.9%, which could produce bioethanol up to 38%. A harmony between bioethanoland biodiesel production from microalgae is needed for the optimum utilization of microalgae.Bioethanol production from microalgae can be done using de-oiled microalgae.